Asian Feminist Pedagogy and Women's Empowerment: A Preliminary Analysis of EGEP - Sun, Lee Myoung (Asian journal of women's studies, 2014)
This is a preliminary analysis of the Ewha Global Empowerment Program (EGEP), a unique educational program for women activists from Asia and Africa offered by Ewha Womans University. Many feminist scholars teaching women's studies or feminist courses at universities and in adult education programs remark on the many changes feminism has produced in terms of awareness regarding gender discrimination, the numerous social advances for empowering women individually and socially and contributing to the creation of real life changes. The capacity of women's studies to bring about individual and social change is not only because of feminist ideology, but also due to the praxis of feminist pedagogy. Accordingly, research and analysis on feminist pedagogy should reveal the praxis and impact of feminisms, and are very important for the expansion of women's studies and feminist education. In this context, the present study, based on the case of EGEP as a field of 'Asian Feminist Pedagogy,' will look at the concrete makeup of the program and analyze the effects of its praxis on its Asian women activist participants. This study has three parts. The first will briefly review the concept and theory of 'Asian feminisms,' which comprise the epistemological backdrop and theoretical framework of EGEP. The second part explains how the concept of Asian Feminisms is being implemented and practiced as feminist pedagogy. The third part analyzes the experience of the Asian women activists who participated in EGEP to show how it empowers women and produces 'Asian women subjects.'